1980
DOI: 10.1002/1097-0142(19800415)45:8<2017::aid-cncr2820450806>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to length of complete remission in adult acute leukemia

Abstract: Two hundred and two adult patients with acute leukemia were analyzed to determine pretreatment and treatment factors that could predict for duration of bone marrow remission. Several factors had a significant effect on remission duration, including morphologic diagnosis (AML greater than ALL greater than AUL), initial blast cell count, age, serum LDH, fibrinogen level, labeling index, and in vitro agar colony growth. Patients who attained a remission quickly or in whom leukemic cells in blood and bone marrow w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
28
1
2

Year Published

1981
1981
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(34 citation statements)
references
References 21 publications
3
28
1
2
Order By: Relevance
“…In most protocols, however, all six subclasses are given the same type of chemotherapy and there appear to be only marginal differences in prognosis between the subclasses and the best prognostic indicator has been the age of the patient (Keating et al, 1980). We have recently described that analysis of the content of TdT and glucocorticoid receptor in leukaemic cells adds significant prognostic information (Skoog et al, 1982).…”
mentioning
confidence: 99%
“…In most protocols, however, all six subclasses are given the same type of chemotherapy and there appear to be only marginal differences in prognosis between the subclasses and the best prognostic indicator has been the age of the patient (Keating et al, 1980). We have recently described that analysis of the content of TdT and glucocorticoid receptor in leukaemic cells adds significant prognostic information (Skoog et al, 1982).…”
mentioning
confidence: 99%
“…Furthermore, longer remissions were much more frequent among AMLpatients whose blood cells showed many colonies and clusters. In a multivariant analysis of several pretreatment factors, Keating et al (1980) found a similar significant correlation between high numbers of clusters and long remission. Since on the other hand, our non-responding group has less colonies and clusters in the peripheral blood than responders, one possible explanation of our results is that in AML the remaining normal haematopoiesis of those leukaemias which can respond to therapy deserts the homing bone marrow and migrates into the peripheral blood.…”
mentioning
confidence: 75%
“…Determination of colony formation has become a useful tool for investigating the abnormal regulation of haematopoiesis. Therefore, several investigators have tried to correlate the in vitro growth pattern of granulopoietic progenitor cells with the prognostic outcome (Keating et al, 1980;Elias & Greenberg, 1977;Moore et al, 1974;Hornsten et al, 1977;Beran et al, 1980;Gustavsson et al, 1981). However, the results have been conflicting due to poor reproducibility and differences in culture technique, sources of colony stimulating activity, classification of growth pattern, therapeutic regimens, selection of patients, and inadequate statistical analysis.…”
mentioning
confidence: 99%
“…Nevertheless, it is intuitive that data gathered after treatment begins can potentially be more useful than pre-treatment data. For example, Keating et al [3] reported that the number of courses needed to achieve CR was inversely related to remission duration and indeed was more predictive of this outcome than pre-treatment covariates. Most attempts to use post-treatment findings to assess risk of relapse have focused on laboratory parameters such as the percentage of bone marrow blasts [4,5], cytogenetics [6,7], leukemia-associated immunophenotypes [8,9], or genetic abnormalities [10][11][12], measured during the induction course or at time of CR.…”
Section: Introductionmentioning
confidence: 99%